Peripheral concentrations of metabolic and inflammatory indicators during transition period and their relationship with postpartum clinical endometritis in dairy cattle - MANIMARAN, AYYASAMY; KUMARESAN, ARUMUGAM; SARKAR, S N; YADAV, ASHA; BOYA, SANJANNA; L, SREELA; LAYEK, S S; MOHANTY, A K; MOOVENTHAN, P; WANKHADE, PRATIK R (The Indian Journal of Animal Sciences, 2019)
The aim of this study was to investigate the peripheral concentration of metabolic and inflammatory indicators during transition period and their relationship in cows that developed clinical endometritis (CE) and remained nonendometritis during later postpartum period. A total of 70 cows were selected and blood was collected from 21 days before calving to 21 days after calving. After adjusting the sampling date based on the actual calving date (â€“21Â±2, â€“7Â±1, 0, 7Â±1, 14Â±1 and 21Â±2 days) and health status, a minimum of 8 samples each from the CE and nonendometritis cows were used at each time point of transition period for the estimation of acute phase proteins (APPs) (haptoglobin, Hp; serum amyloid A, SAA; and alpha-1 acid glycoprotein, AGP), pro-inflammatory cytokines (IL-1ô€…, TNF-ô€„, IL-6 and IL-8) and energy indicators (NEFA, BHBA, Leptin and IGF-I) using bovine specific ELISA kits. APPs (Hp, SAA and AGP), cytokines (IL-1ô€…, TNF-ô€„, IL-6) and energy indicators (NEFA, BHBA, Leptin) levels significantly increased, while IL-8 and IGF-I levels significantly decreased in transition cows that eventually developed to CE compared to the cows which remained non-endometritis during 22â€“47 days postpartum. It is concluded that cows that diagnosed as CE during postpartum period were experienced negative energy balance and compromised their immune status during transition period.